Pengaruh Tingkat Pendidikan dan Jumlah Penduduk Terhadap Tingkat Pengangguran Di Provinsi Jawa Timur - Dewi Afifah; Nurul Hanifa (Universitas Negeri Surabaya, 2022)
Unemployment is a macroeconomic problem that is still a concern and discussion of the government. Unemployment is a problem in the economy that can disrupt the development process. This study aims to analyze the effect of education level and population on unemployment rate in East Java Province 2017-2021. This study uses a multiple linear regression research from method with panel data and uses estimation technical fixed effect model. Testing data using E-Views 12 and obtained results that the level of education and population partially had a positive and significant effect on unemployment rate. The level of education and population simultaneously have a significant effect on unemployment rate.